Remittances and labor supply in post-conflict Tajikistan - Patricia Justino; Olga N. Shemyakina (IZA Journal of Labor & Development, 2012)
We analyze the impact of remittances on the labor supply of men and women in post-conflict Tajikistan. Individuals from remittance-receiving households are less likely to participate in the labor market and supply fewer hours when they do. The results are robust to different measures of remittances and migration. When we differentiate between regions by their exposure to the 1992-1998 armed conflict, we observe that the negative effect of remittances on the labor supply of women is primarily driven by women from the regions more exposed to fighting and destruction during the war. Remittances have a similar negative effect on the supply of labor hours worked across all regions, both for men and women. Further, in the households that do not have migrants, remittances have no effect on the labor supply by males, suggesting that migration and not remittances is the primary factor explaining male labor force participation.
Keywords: J22; F22; F24; O12; 330; migration; remittances; labor markets; Tajikistan; gender; armed conflict; Rücküberweisungen; Erwerbstätigkeit; Geschlecht; Politischer Konflikt; Tadschikistan